Preface of the 3rd International Joint Conference on Water Distribution Systems Analysis & Computing and Control for the Water Industry (WDSA/CCWI 2024) - Stefano Alvisi; Marco Franchini; Valentina Marsili; Filippo Mazzoni (Engineering Proceedings)
The 3rd International Joint Conference on Water Distribution Systems Analysis & Computing and Control for the Water Industry (WDSA/CCWI 2024)—held in Ferrara, Italy, 1–4 July 2024—aimed at involving national and international institutions, public and private companies, professionals, academics, and researchers operating in the field of water distribution and drainage systems management [...]